2014
DOI: 10.1590/0103-8478cr20130873
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid on antioxidant activity and betacyan in production from leaves of Alternanthera tenella

Abstract: This research investigates effects of salicylic acid (an abiotic elicitor) on the antioxidant activity and betacyan production from leaves of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 30 publications
1
7
1
1
Order By: Relevance
“…The authors concluded that this activity could only be attributed to these flavones and not to betalains [ 69 ]. These results disagree with those reported by Rodrigues-Brandão [ 103 ], since the antioxidant activity was related to the betacyanins accumulated by A. tenella growing in vitro. Both increased with the addition of salicylic acid to the culture medium.…”
Section: Amaranthaceaecontrasting
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that this activity could only be attributed to these flavones and not to betalains [ 69 ]. These results disagree with those reported by Rodrigues-Brandão [ 103 ], since the antioxidant activity was related to the betacyanins accumulated by A. tenella growing in vitro. Both increased with the addition of salicylic acid to the culture medium.…”
Section: Amaranthaceaecontrasting
confidence: 99%
“…The plant has been also used as diuretic [ 100 , 101 ]. Laboratorial experiments have revealed that A. tenella extracts have immunomodulatory, antioxidant, anti-hyperalgesic, antimicrobial and antiparasitic properties [ 85 , 96 , 101 , 102 , 103 , 104 ]. As reported for A. brasiliana , these activities have been generally attributed to the phenols, particularly flavonoids.…”
Section: Amaranthaceaementioning
confidence: 99%
“…Los resultados obtenidos en esta gramínea de importancia alimenticia y económica, permiten confirmar la participación del AS en la inducción de síntesis de fenoles en las plantas (Dong et al, 2010), a la vez que reafirman su colaboración en la producción de metabolitos secundarios tal como se ha reportado en Alternanthera tenella (Rodrigues-Brandão et al, 2014), Saccharum officinarum y Calendula officinalis L. (Pacheco et al, 2013); además, dan la pauta para proponer su uso como herramienta en la inducción de tolerancia a plagas (García et al, 2003) y enfermedades del grano en maíz (Bakan et al, 2003), y para incrementar el poder antioxidante de este cereal, que se traduce en beneficios potenciales en la salud humana (Adom y Liu, 2002;Liu, 2007).…”
Section: Resultados Y Discusiónunclassified
“…DPPH solution in ethanol was prepared in the concentration of 28 mg mL -1 . This concentration was used in previous studies in order to show absorbance at 515 nm between 0.6 and 0.7 u.a [2,18,19].…”
Section: Methodsmentioning
confidence: 99%